SAT0079 Association of alcohol consumption and disease activity in japanese patients with rheumatoid arthritis: analysis of the iorra cohort. (15th June 2017) - Shimizu, Y; Tanaka, E; Inoue, E; Ochiai, M; Yamaguchi, R; Sugimoto, N; Nakajima, A; Ikari, K; Taniguchi, A; Yamanaka, H
Abstract : Background: While the results of several observational studies suggest that light-to-moderate alcohol consumption may decrease the risk for susceptibility to or severity of rheumatoid arthritis (RA) (1–3), findings regarding the effect of alcohol consumption on RA disease activity are conflicting. Furthermore, there are few reports of longitudinal studies regarding the effect of alcohol consumption on RA disease activity. In addition, although alcohol consumption in the Japanese general population was lower than that in European countries, according to the 2011 World Health Organization's Global Status Report on Alcohol and Health, there are few reports specifically concerning alcohol consumption in Japanese RA patients. Objectives: To examine the longitudinal relationship between alcohol consumption and changes in disease activity in patients with RA using the Institute of Rheumatology, Rheumatoid Arthritis (IORRA) cohort database. Methods: Subjects were RA patients who participated in the IORRA cohort study between October 2014 and October 2015. Patients were assigned to one of 5 groups according to alcohol-drinking status at baseline: the non-drinking group, drinking group 1 (0 g < amount of drinking per day [Alco-drink] ≦14 g), drinking group 2 (14 g < Alco-drink ≦28 g), drinking group 3 (28 g < Alco-drink ≦50 g), and drinking group 4 (50 g < Alco-drink). Multiple regression analyses were used to examine the relationship between alcohol consumption and baseline DAS28, and change in DAS28 between baseline and 1 year. Results: Data from a total of 4, 695 Japanese patients with RA (female: 86.6%, mean age: 61.3 years old, mean disease duration: 15.2 years, and mean DAS28: 2.5) were analyzed. The number of patients and their characteristics (% female, mean age, mean disease duration, mean DAS28 at baseline/after 1 year) in the non-drinking group, and drinking groups 1, 2, 3, and 4 were 2, 735 (92.8%, 64.0 years old, 16.1 years, 2.7/2.7); 646 (89.9%, 58.7 years old, 14.8 years, 2.4/2.5), 497 (82.5%, 56.7 years old, 13.8 years, 2.3/2.3), 444 (71.6%, 56.4 years old, 13.0 years, 2.3/2.3), and 373 (58.2%, 57.5 years old, 13.7 years, 2.2/2.3), respectively. Baseline DAS28 in drinking groups 2 (p=0.02), 3 (p<0.01), and 4 (p<0.01) was significantly lower than that in the nondrinking group. Multivariate regression analysis revealed that there was no association between alcohol-drinking status and the change in DAS28 at 1 year, after adjusting for DAS28 at baseline. Conclusions: Although moderate-to-heavy alcohol consumption was associated with lower baseline DAS28 in patients, alcohol drinking status was not associated with change in disease activity, as measured by DAS28, at 1-year follow-up. References: Di Giuseppe D. BMJ, 2012 Jul 10;345:e4230. Kallberg H. Ann Rheum Dis, 2009;68:222–7. Maxwell JR. Rheumatology (Oxford), 2010;49:2140–6. Disclosure of Interest: Y. Shimizu: None declared, E. Tanaka Consultant for: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Pfizer, Takeda Pharmaceutical, and Ayumi Pharmaceutical., E. Inoue: None declared, M. Ochiai: None declared, R. Yamaguchi: None declared, N. Sugimoto Speakers bureau: Takeda Pharmaceutical and Bristol Myers Squibb., A. Nakajima Consultant for: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company., Speakers bureau: Bristol-Meyers, Mitsubishi Tanabe Pharma, Nippon Kayaku Co. Ltd., Novartis Pharma, Pfizer, Siemens Healthcare Diagnostics K.K. and Takeda Pharmaceutical Company., K. Ikari Grant/research support from: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., Speakers bureau: Astellas, UCB, Bristol-Meyers, Pfizer, Eisai, Tanabe-Mitsubishi, Chugai, AbbVie, Janssen Pharmaceutical, Otsuka, Kaken, Asahi-Kasei, Hisamitsu and Takeda., A. Taniguchi Grant/research support from: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., Speakers bureau: AbbVie, Eisai, Takeda, Tanabe-Mitsubishi, Teijin Pharma, Pfizer., H. Yamanaka Grant/research support from: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi- Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Consultant for: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers., Speakers bureau: MSD, Ayumi, AbbVie, Eisai, Ono, Astellas, Daiichi-Sankyo, Taisyo-Toyama, Takeda, Tanabe-Mitsubishi, Chugai, Teijin Pharma, Torii, Nippon Shinyaku, Pfizer. UCB. Nippon Kayaku, YL biologics, Bayer and Bristol-Meyers.